Association between household solid fuel usage and trajectories of multimorbidity among middle-aged and older adults: a nationwide population-based cohort study - Li, Yiting; Wu, Bingjie; Fan, Bingbing; Lv, Jiali; Li, Chunxia; Su, Chang; Liu, Aidong; Zhang, Tao (Frontiers in Public Health, 2024)
Background: This study aims to explore the effect of household solid fuel usage on the multimorbidity trajectories among middle-aged and older adults. Methods: Based on the 2011-2018 China Health and Retirement Longitudinal Study, the group-based trajectory modeling and the multinomial logistic regression model were used to explore the relationship multimorbidity trajectories of older adults with different fuel types, duration of solid fuel usage and potential interaction with PM2.5. Three multimorbidity trajectory patterns were identified by group-based trajectory modeling and labelled as “Non-chronic morbidity” (no disease increase), “Newly-developing multimorbidity” (diseases grew from 0 to 2), and “Multi-chronic multimorbidity” (diseases grew from 2 to 4). Results: Compared to “Non-chronic morbidity”, solid fuel was significantly associated with adverse multimorbidity trajectories, with odds ratio (OR) and 95% confidence interval (CI) 1.33 (1.11, 1.60) and 1.35 (1.11, 1.60) for newly-developing and multi-chronic group, respectively. An adverse multimorbidity trajectory tended to be established with longer durations of solid fuel use compared to “Non-chronic morbidity”. For “Newly-developing multimorbidity”, the OR (95%CI) for 1-7 years and ≥8 years of solid fuel use were 1.16 (0.94, 1.42) and 1.41 (1.12, 1.76), respectively, with P trend <0.001, while in “Multi-chronic multimorbidity”, those were 1.25 (1.07, 1.47) and 1.68 (1.41, 2.00), respectively, with P trend <0.001. In the interaction analysis, the association between solid fuel usage and trajectories was significant only in areas where PM2.5 was lower than 50 μg/m3. Conclusions: For middle-aged and older Chinese population, a higher risk of multimorbidity trajectory is associated with household solid fuel usage, especially in the area with lower PM2.5.